SOCIAL MEDIA IN HIGHER EDUCATION AND ITS EFFECT ON GLOBAL CHALLENGE - Mardiana, Harisa (Indonesian Journal of Learning and Instruction, 2019)
My interest of doing the research is to investigate the effect of social media in higher education on globalization. As the learning process changes, social media takes a step ahead to present itself to support the learning process in campus. Furthermore, students can communicate and share everything about the content of learning with their peers, lecturers, staff and others. The changes refer to available demand on access toward contents, schedules, and news, in different time, location and digital devices that provide the user with the chance to interact through comments, feedback and creative participation. The objective of the research is to describe the problems faced by the stakeholders of the higher education regarding the use of social media in higher education context. The research found that ignorance or lack of preparation were the most significant challenges. In fact, innovation in learning has converged with all application in mobile device, and the change of learning has led to the new management. The design of the research was a mixed method research quantitative and qualitative method. Data collection technique was done through observation, questionnaires and interview and data analysis. The result of the research showed that social media in higher education need to be implemented in university. And the effect in higher education needed to be incorporated into curriculum for the learning by social media and the adoption of social media as a teaching and learning process including the program of e-learning.